On the daimonion of Socrates : human liberation, divine guidance and philosophy - Plutarch (Sapere (Darmstadt, Germany), 2010)
Plutarch's dialogue On the daimonion of Socrates is a unique combination of exciting historical romance and serious philosophical and religious discussion. The volume offers a range of essays on themes providing further insights into this masterly literary piece: on the historical, religious and philosophical background and on thematic connections with other works by Plutarch.